Top Gear : The Official Annual 2009 - Published by BBC Children's Books (London BBC Children's Books, 2008)
"Top Gear" books are for younger fans of the TV programme, not suitable for adults. Relive your favourite moments from "Top Gear" in this 96-page action-packed annual. Take numerous quizzes, complete all kinds of activities and revisit the Polar and Africa Challenges. This annual will not disappoint "Top Gear" fans. -- Publisher details.
Include Colour Illustrations
Keywords: Automobiles -- Top Gear (Television program)